2019
DOI: 10.3390/nu11071523
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value and Biological Activity of Concentrated Protein Fraction of Potato Juice

Abstract: Potato protein is recognized as one of the most valuable nonanimal proteins due to the high content of essential amino acids. So far, it has not been used in human nutrition on a large scale due to technological limitations regarding its acquisition. In this study, the protein fraction of potato juice was concentrated with the use of membrane separation. The obtained potato juice protein concentrate (PJPC) was characterized in terms of nutritional value and biological activity, and the amino acid composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 71 publications
4
65
0
1
Order By: Relevance
“…The digestibility of the received preparations was determined in vitro with the method simulating multi‐enzymatic two‐stage (gastric and intestinal) digestion (Butts et al , ; Kowalczewski et al , ). The samples were collected after intestinal digestion.…”
Section: Methodsmentioning
confidence: 99%
“…The digestibility of the received preparations was determined in vitro with the method simulating multi‐enzymatic two‐stage (gastric and intestinal) digestion (Butts et al , ; Kowalczewski et al , ). The samples were collected after intestinal digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is necessary to find consumer-friendly plant proteins to replace those from allergenic ones. Still, some of the valuable proteins sources, such as those obtained from the fraction of potato juice, have not been frequently used [11]. The limitations are related to the unsolved technological problems.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were previously reported for AJ exposed to UV action, however, in these studies UV-treated AJ revealed no cytotoxic effect on normal intestinal cells but exhibited the significantly induced inhibitory effect on the growth of human colon cancer cells 35 . On the other hand, the data published by Kowalczewski et al 36 indicated that pure potato juice exhibited selective cytotoxic activity against cancer and normal colon cells.…”
Section: Microbiological Properties Of the Ntap-treated Apple Juicementioning
confidence: 98%